Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00221-005-0266-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrical activation of the human vestibulo-sympathetic reflex

Abstract: Muscle sympathetic nerve activity (MSNA) is modulated on a beat-to-beat basis by the baroreflex. Vestibular input from the otolith organs also modulates MSNA, but characteristics of the vestibulo-sympathetic reflex (VSR) are largely unknown. The purpose of this study was to elicit the VSR with electrical stimulation to estimate its latency in generating MSNA. The vestibular nerves of seven subjects were stimulated across the mastoids with short trains of high frequency, constant current pulses. Pulse trains we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…VSR in humans has been found to be a mediator of cardiovascular stress (Dyckman et al 2007, Saunder et al 2008 and to even have shorter response latency than the baroreflex (Kaufman et al 2002 andVoustianiouk et al 2006). The latter finding indicates that the VSR could be the first line-of-defense to cardiovascular stress and thus could play a vital role in maintaining astronaut orthostatic tolerance.…”
Section: Vestibular Motivations For Artificial Gravitymentioning
confidence: 99%
“…VSR in humans has been found to be a mediator of cardiovascular stress (Dyckman et al 2007, Saunder et al 2008 and to even have shorter response latency than the baroreflex (Kaufman et al 2002 andVoustianiouk et al 2006). The latter finding indicates that the VSR could be the first line-of-defense to cardiovascular stress and thus could play a vital role in maintaining astronaut orthostatic tolerance.…”
Section: Vestibular Motivations For Artificial Gravitymentioning
confidence: 99%
“…Arterial baroreceptor mechanisms play an important role in regulating peripheral vasoconstriction during postural alterations (23). In addition, there is considerable evidence from studies in animals (6,8,10,11,21,22,32) and humans (1,4,12,23,26,28,30) that the vestibular system also participates in triggering increases in vasomotor activity during movements that promote peripheral blood pooling.Experiments conducted on anesthetized (13, 15) and conscious (32) cats demonstrated that the vestibular system influences on different vascular beds are not equivalent. Electrical stimulation of vestibular afferents produces opposite changes in the activity of sympathetic nerve fibers innervating arterioles in skeletal muscle of the upper and lower body (15) and reciprocal changes in forelimb and hindlimb blood flow (13).…”
mentioning
confidence: 99%
“…In humans, using head-down rotation (HDR) as a model to activate the vestibular otolith organs, we have demonstrated marked increases in MSNA and peripheral vasoconstriction (15,31,[33][34][35]43). Other studies have supported the presence of the VSR in humans (1,12,19,46). Studies examining changes to the vestibular system after BR are sparse.…”
mentioning
confidence: 96%